Sigmoidal diagnostics with SOHO/CDS - Del Zanna, G. (2002)
During the third Whole Sun Month Campaign (August 18 - September 14, 1999), the evolution of the active region NOAA 8668 was followed during its meridian passage and at the limb (Sigmoid JOP 106), with simultaneous observations with the Solar and Heliospheric Observatory (SOHO), and with other instruments, both satellite and ground-based. On August 21st, a small flare, associated with a brightening of the sigmoidal structure, occurred. SOHO Coronal Diagnostic Spectrometer (CDS) observations of this small flare are presented. Coronal temperatures and densities of the sigmoid are estimated. High transition region densities (in the range 2.5-7 × 10 11 cm -3), obtained using O IV, are present in the brightenings associated with the flare. At coronal level, high temperatures of at least 8 MK were reached, as shown by strong Fe XIX emission. After this small flare, relatively strong blue-shifts (⋍ 30 km/s) are observed in coronal lines, located at the two ends of a small loop system associated with the sigmoid.